Mapping the Transition of Adolescents to Adult HIV Care: A Mixed-Methods Perspective from the Cape Town Metropole, South Africa - Charné Petinger; Brian van Wyk; Talitha Crowley (Tropical Medicine and Infectious Disease)
(1) Background: Globally, an estimated 1.7 million adolescents (aged 10–19 years) were living with HIV in 2023, with 82% residing in sub-Saharan Africa. For ALHIV, transitioning to adult care involves assuming responsibility for their own health and disease management, posing significant challenges to persistent engagement in care. There is a paucity in health policies guiding this transition in many sub-Saharan African countries. Overburdened and poorly functioning health systems struggle to provide optimal care for ALHIV amidst the rising HIV pandemic in this priority population. (2) Methods: This study employed a mixed-methods design, comprising a descriptive qualitative study with healthcare workers and managers and a cross-sectional survey to examine the practices and pathways in which the transition to adult HIV care occurs in the Cape Town Metropole, South Africa. (3) Results: We delineate three distinct ways in which transition occurs (transfer-only, adolescent-friendly, and supportive transition). A successful transition involves a sufficient level of self-management of their chronic condition and healthcare journey, which is preceded by adequate preparation pre-transition, and the monitoring of engagement post-transition. This ideally requires developing relevant health policies and implementing guidelines signaling political will and providing the impetus and agency of implementation at the service level in South Africa.